ANTIFUNGAL ACTIVITY TEST OF THE COMBINATION OF PAPAYA LEAF (Carica papaya L.) AND BASIL LEAF (Ocimum x africanum Lour) EXTRACTS AGAINST THE GROWTH OF Candida albicans - Pratama, Dimas Feriza Pratama; Suswidiantoro, Vicko; Daskar, Annajim; Safutri, Wina (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Fungal infections are common health problems, one of which is caused by Candida albicans. The use of synthetic antifungal agents in treatment can lead to side effects and resistance risks, thus necessitating safer natural alternatives. Papaya leaves (Carica papaya L.) and basil leaves (Ocimum x africanum Lour) are known to contain active compounds such as flavonoids, alkaloids, saponins, steroids, and tannins, which have potential as antifungal agents. The combination of these two plant extracts was used to enhance antifungal effectiveness through possible synergistic effects of their active compounds, with the expectation of yielding a more optimal inhibitory effect against Candida albicans. This study aimed to determine the effectiveness of a combination of papaya and basil leaf extracts in inhibiting the growth of Candida albicans. The research was conducted experimentally using a Completely Randomized Design (CRD) with five treatment groups and four replications. The antifungal activity was tested using the disc diffusion method with extract combinations formulated in 96% ethanol at concentrations of (18.75% : 18.75%), (37.5% : 12.5%), and (56.25% : 6.25%), as well as a negative control (aquadest) and a positive control (ketoconazole 15 μL). One-Way ANOVA analysis showed a significant difference between treatments (p < 0.05). Further analysis using Tukey HSD revealed no statistically significant differences between the three extract combination groups. However, P3 exhibited the highest inhibition zone (4.73 ± 0.91 mm), while P1 showed the lowest (3.45 ± 0.65 mm), and P2 was intermediate (3.98 ± 0.65 mm). All three combinations showed statistically significant differences compared to the negative control (0 mm) and the positive control (6.50 ± 0.83 mm). Thus, although no significant difference was observed between the combination groups, all combinations demonstrated statistically significant antifungal activity against Candida albicans compared to the negative control. In conclusion, the combination of papaya and basil leaf extracts possesses antifungal activity against Candida albicans, although the effectiveness is not yet optimal. Further research is recommended with increased extract concentrations and development into pharmaceutical dosage forms such as gels or ointments as alternative topical antifungal treatments.